A comparative evaluation of graft uptake and audiological results of temporalis fascia graft vs reinforced sliced tragal cartilage in type 1 tympanoplasty - Swuro, Voto; Aggarwal, Ankita; Bhagat, Sanjeev; Sahni, Dimple; Sharma, Dinesh; Yadav, Vishav; Goel, Khushboo (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: Numerous grafting materials have been applied for repair of tympanic membrane (TM) in chronic otitis media patients. This study aimed to compare the anatomical and audiological results of temporalis fascia alone versus reinforced sliced cartilage in type 1 tympanoplasty. Methods: A prospective study was conducted on 50 patients of age group 15-55 years. Patients were randomly divided into two groups, each group having 25 patients. In group I patients under went type I tympanoplasty with temporalis muscle fascia alone and group II patients with sliced tragal cartilage reinforced to temporalis fascia. Post operatively all patients were followed on 30th, 60th and 90th day. In the last follow up, assessment of graft uptake was done and pure-tone audiometry was performed to evaluate air-bone gap closure. The data so obtained were collected and analysed using appropriate statistical tests. Results: Overall graft uptake rate in group I (TF alone) was 84%, whereas in group II (TF+ reinforced sliced cartilage) was 92% (p=0.5). The mean post op ABG improved to 16.17±6.26 dB and 16.56±5.25 dB respectively in group I and II. There was significant hearing improvement in each group but no statistical significant difference was observed in post-op ABG between the two groups. Conclusions: Reinforced sliced tragal cartilage technique is a good alternative to temporalis fascia alone in terms of graft uptake and prevention of disease recurrence, especially for large and subtotal perforations but additive effect of cartilage slicing in hearing gain still remains little controversial.